2022
DOI: 10.1590/1413-785220223006e256048
|View full text |Cite
|
Sign up to set email alerts
|

Grafts for Anterior Cruciate Ligament Reconstruction: Systematic Review and Meta-Analysis

Abstract: Objective: This study proposes to systematically review the literature and compare data on (1) function, (2) pain, (3) return to sport, and (4) complications after anterior cruciate ligament (ACL) reconstruction with quadriceps tendon autograft (QT) and hamstring tendon autograft (HT). Methods: In June 2021, a systematic review of the EMBASE, MEDLINE/PubMed, Cochrane Central Register of Controlled Trials, and LILACS databases was performed, based on PRISMA guidelines. The search strategy included the keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(153 reference statements)
0
3
0
Order By: Relevance
“…Of the 2598 studies initially identified from the search strategy, a total of 50 systematic reviews (36 systematic reviews with meta‐analyses, 14 systematic reviews alone) were included in the final quality assessment (Figure 1) [1‐7, 10‐13, 16, 19, 21‐23, 25‐29, 31‐33, 35, 38‐42, 44, 46, 48, 52, 54, 58‐60, 65‐69, 71‐75, 77]. Cohen's κ Scores were 0.73, 0.75 and 0.74 at the title/abstract, full‐text screening and AMSTAR‐2 assessment stages, respectively, indicating substantial agreement at all phases of the review.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 2598 studies initially identified from the search strategy, a total of 50 systematic reviews (36 systematic reviews with meta‐analyses, 14 systematic reviews alone) were included in the final quality assessment (Figure 1) [1‐7, 10‐13, 16, 19, 21‐23, 25‐29, 31‐33, 35, 38‐42, 44, 46, 48, 52, 54, 58‐60, 65‐69, 71‐75, 77]. Cohen's κ Scores were 0.73, 0.75 and 0.74 at the title/abstract, full‐text screening and AMSTAR‐2 assessment stages, respectively, indicating substantial agreement at all phases of the review.…”
Section: Resultsmentioning
confidence: 99%
“…Latest review shows that QT and HT autografts have comparatively good results in ACLR without significant differences regarding function, pain, and rupture after surgical intervention [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the flexors side, hamstring weakness was more prevalent and significant in short term observation of HT patients when compared to others. [16,17] Yet another important factor to be considered while choosing ACL graft are complication types and rates. The most common morbidity after ACLR is anterior knee pain which was proved to be significantly related with BPTB graft.…”
Section: Autograftsmentioning
confidence: 99%